In-situ Measurement of Self-Atom Diffusion in Solids Using Amorphous Germanium as a Model System. Issue 1 (December 2018) - Hüger, Erwin; Strauß, Florian; Stahn, Jochen; Deubener, Joachim; Bruns, Michael; Schmidt, Harald
Abstract We presentin-situ self-diffusion experiments in solids, which were carried out by Focussing Neutron Reflectometry on isotope multilayers. This new approach offers the following advantages in comparison to classicalex-situ measurements: (1) Identification and continuous measurement of a time dependence of diffusivities, (2) significant reduction of error limits of diffusivities, and (3) substantial reduction of the necessary experimental time. In the framework of a case study, yet unknown self-diffusivities in amorphous germanium are measured at various temperatures quasi-continuously, each during isothermal annealing. A significant decrease of diffusivities as a function of annealing time by one order of magnitude is detected that is attributed to structural relaxation accompanied by defect annihilation. In metastable equilibrium the diffusivities follow the Arrhenius law between 375 and 412 °C with an activation energy of Q = (2.11 ± 0.12) eV. The diffusivities are five orders of magnitude higher than in germanium single crystals at 400 °C, mainly due to the lower activation energy.